2009
DOI: 10.4070/kcj.2009.39.11.494
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Left Ventricular Noncompaction Cardiomyopathy Accompanied by Severe Mitral Regurgitation

Abstract: Isolated left ventricular noncompaction cardiomyopathy (IVNC) is a cardiomyopathy thought to be caused by arrest of normal embryogenesis of the endocardium and myocardium. This abnormality is often associated with other congenital cardiac defects. A 21-year-old man presented to the emergency department with worsening exertional dyspnea during the previous 2 months. Two-dimensional and Doppler echocardiography revealed an enlarged left atrium (LA) and a markedly dilated left ventricle (LV) with preserved LV sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 15 publications
2
10
0
2
Order By: Relevance
“…Clinical presentation is variable and can be any combination of heart failure, arrhythmias, embolic events and conduction disorders [ 1 ]. Severe mitral regurgitation associated with ILVNC has been also been documented recently [ 2 , 4 , 5 ]. Long-term outcome of patients with ILVNC is not clear, but a recent small study showed worse prognosis than in the general population, but similar to dilated cardiomyopathy patients [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical presentation is variable and can be any combination of heart failure, arrhythmias, embolic events and conduction disorders [ 1 ]. Severe mitral regurgitation associated with ILVNC has been also been documented recently [ 2 , 4 , 5 ]. Long-term outcome of patients with ILVNC is not clear, but a recent small study showed worse prognosis than in the general population, but similar to dilated cardiomyopathy patients [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Management of patients with ILVNC is same as that of other cardiomyopathies that require treatment for heart failure, and appropriate prevention and management of complications that include arrhythmias, conduction abnormalities, systemic emboli and valvular dysfunction like severe mitral valve regurgitation [ 3 ]. There have been few cases reported of ILVNC associated with severe mitral regurgitation [ 2 , 4 , 5 ]. But due to limited data, appropriate management and their long-term outcome is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Due to secondary enlargement of the annulus or possible subvalvular abnormality, VNC of the LV could be accompanied by moderate‐to‐severe mitral regurgitation. Several studies have addressed the clinical findings in this situation and surgical treatment . However, the surgeries mainly focused on valve problems.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have addressed the clinical findings in this situation and surgical treatment. [7][8][9] However, the surgeries mainly focused on valve problems. One case partially excluded the trabeculated ventricular cavity, 8 and none performed any surgical treatment to the abnormal myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Неком-пактный миокард левого желудочка часто сочета-ется с митральной региргутацией при сохраненной функции левого желудочка [26,27]. При такой соче-танной патологии наблюдаются склероз и кальци-фикация створок митрального клапана [28], и как следствие, ретракция створок [29].…”
unclassified